Reaching consensus on definitions for food and physical activity policies: experience from the Policy Evaluation Network. (29th November 2022) - Kelly, Liam; Twohig, Cliona; Woods, Catherine B; Luszczynska, Aleksandra; Murrin, Celine; Lien, Nanna; Meshkovska, Biljana; Kamphuis, Carlijn B M; Poelman, Maartje P; Terragani, Laura; Forberger, Sarah; Hebestreit, Antje; et al.
Abstract: Background: An upsurge in policy evaluation research within public health sciences has led to multi-disciplinary research networks like the 'Policy Evaluation Network' (PEN). This multi-disciplinary collaboration highlighted the need for consensus on clear, common terminology and definitions to facilitate the multi-disciplinary research. This article outlines the development process of the PEN definitions glossary tool, with a focus on the key domains of policy design, implementation and outcomes as they apply to physical activity, sedentary behaviour and dietary behaviours. Methods: A project specific participatory process was undertaken, involving PEN researchers ( n = 48) from seven European countries across various disciplinary backgrounds. All involved researchers were invited to identify and collate definitions that were commonly used in their research field. Terms and definitions were discussed and debated during three online workshops. Subsequently, the definitions were discussed and refined until consensus was reached. Results: Consensus definitions for 93 terms related to the evaluation of policy design, implementation and outcomes are provided. Consensus was reached on a range of terms where the terms were understood and used differently across represented disciplines (e.g. 'Outcome' and 'Impact'). A conceptual 'Inter-relations in policy-related concepts' diagram was developed to enable navigation through an online database with key terms. Conclusions: The definitions resulting from this participatory process has supported PEN researchers and practitioners across disciplines to reach a shared understanding of different terms related to policy evaluation. Thus, providing a platform for avoiding conflicting use of the same terms in differing contexts over the course of the PEN work programme, facilitating clear and consistent communication, and allowing for clarity within collaborative multi-disciplinary projects and in public-facing messages.